2018
DOI: 10.1021/acs.jafc.8b01456
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Salinity and CaCO3 Affects the Physiology and Fatty Acid Metabolism in Portulaca oleracea

Abstract: As a result of the extreme conditions that usually occur in Mediterranean climates, the objective of this work is to study the combined and/or separate effects of saline and alkaline stresses in Portulaca oleracea. The study was carried out to determine the nutritional food potential in relation to plant physiological parameters. The results show that alkaline media in which CaCO was present did not affect growth but exposure to 100 mM NaCl decreased it greatly. Fatty acid content increased under all stress co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Stems were rich in moisture (89.93 mg g −1 ) and anthocyanins (4.61 µg g −1 DM), whereas leaves showed high amounts of chlorophyll a, chlorophyll b, and total chlorophylls. Thus, P. oleracea appears to be an efficient photosynthetic plant, which is confirmed by Bessrour et al [73] experimental trials where severe stress conditions revealed a slight decrease in chlorophyll amounts in this species.…”
Section: Proximate Compositionsupporting
confidence: 74%
“…Stems were rich in moisture (89.93 mg g −1 ) and anthocyanins (4.61 µg g −1 DM), whereas leaves showed high amounts of chlorophyll a, chlorophyll b, and total chlorophylls. Thus, P. oleracea appears to be an efficient photosynthetic plant, which is confirmed by Bessrour et al [73] experimental trials where severe stress conditions revealed a slight decrease in chlorophyll amounts in this species.…”
Section: Proximate Compositionsupporting
confidence: 74%
“…Purslane also has medicinal properties (Uddin et al, 2014;Petropoulos et al, 2016), and it has been listed among the most common used plants for medicinal purposes by WHO (Naeem and Khan, 2013). Interest in cultivating purslane as a vegetable has increased since its bioactive compounds, such as omega-3 fatty acid (Palaniswamy et al, 2001;Teixeira et al, 2010;Bessrour et al, 2018) and ascorbic acid, together with other antioxidants, vitamins, and essential amino acids have been identified (Franco et al, 2011). According to Yazici et al (2007), purslane is a succulent dicot halophyte, which is drought-and salt-tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that the addition of 10% and 20% of CaCO 3 to soil increased EL, which might damage cell membrane integrity and induce stress in tomato plants. Lee and Kim [26] and Bessrour et al [29] showed that the application of CaCO 3 to soil resulted in a slight reduction in leaf SPAD value, but it had no major impact on leaf chlorophyll content. However, we found that the exposure of tomato plants to 5% and higher concentrations caused a significant decrease in leaf SPAD value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on agricultural crops have shown that the addition of excessive levels of CaCO 3 as an amendment adversely affects plant growth by decreasing parameters such as the number of fruits, plant height, stem diameter, plant fresh and dry weight, number of branches [25][26][27], canopy size, and fruit yield [28]. Lee and Kim [26] and Bessrour et al [29] observed a slight reduction in leaf chlorophyll content caused by the application of CaCO 3 . On the other hand, an excess of CaCO 3 in the soil diminishes the availability of P and micronutrients to plants [10,11].…”
Section: Introductionmentioning
confidence: 99%